2018
DOI: 10.1186/s12874-018-0586-7
|View full text |Cite
|
Sign up to set email alerts
|

Retention strategies in longitudinal cohort studies: a systematic review and meta-analysis

Abstract: BackgroundParticipant retention strategies that minimise attrition in longitudinal cohort studies have evolved considerably in recent years. This study aimed to assess, via systematic review and meta-analysis, the effectiveness of both traditional strategies and contemporary innovations for retention adopted by longitudinal cohort studies in the past decade.MethodsHealth research databases were searched for retention strategies used within longitudinal cohort studies published in the 10-years prior, with 143 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
294
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 327 publications
(314 citation statements)
references
References 166 publications
16
294
2
2
Order By: Relevance
“…A recent systematic review and meta-analysis reported average retention to longitudinal cohort studies of 73.5% (Teague et al, 2018). The retention observed within this study (76.74%) is broadly consistently with this average and compares favourability to retention observed by Palan and Schitter (2018) and Sheeran and Conner (2019) in other studies conducted on the Prolific platform with shorter follow-up periods (2 weeks and 3 months respectively).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…A recent systematic review and meta-analysis reported average retention to longitudinal cohort studies of 73.5% (Teague et al, 2018). The retention observed within this study (76.74%) is broadly consistently with this average and compares favourability to retention observed by Palan and Schitter (2018) and Sheeran and Conner (2019) in other studies conducted on the Prolific platform with shorter follow-up periods (2 weeks and 3 months respectively).…”
Section: Discussionsupporting
confidence: 81%
“…The retention rate is particularly promising given that very low burden to researchers in managing participant retention and recontact. While we did not formally track researcher time, we estimate that management of the entire follow-up recruitment process Teague et al (2018), who reported higher retention rates in cohorts with a greater proportion of female participants and with examinations from within individual cohort studies that have reported higher attrition among male respondents (e.g. Radler & Ryff, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most notably, 43% of the survey respondents who said they use Instagram affirmed that our study account influenced their decision to continue their participation, which aligns with the finding from Teague et al 16 that using more social media and other emerging retention strategies has been shown to strengthen retention. Though this finding was unexpected given that a substantially lower proportion of participants said they were actually following the account, it is possible that knowing the study used Instagram affected perceptions of the study being youth friendly, thereby increasing their likelihood to continue participating.…”
Section: Discussionsupporting
confidence: 87%
“…15 However, methods for innovative, technology-based engagement with study participants may need to expand as adolescents' interaction with technology evolves. In a meta-analysis of retention strategies in longitudinal cohorts, Teague et al 16 found that studies that used a greater number of "emerging retention strategies" (e.g. social media and SMS) achieved higher retention rates.…”
Section: Justification For Instagrammentioning
confidence: 99%